Novel Nanocrystal Injection of Insoluble Drug Anlotinib and Its Antitumor Effects on Hepatocellular Carcinoma - Luo, Mei; Sun, Huiwei; Jiang, Qiyu; Chai, Yantao; Li, Congshu; Yang, Bin; Hong, Zhixian (Frontiers in Oncology, 2021)
The molecularly targeted agent anlotinib offers a novel therapeutic strategy against advanced hepatocellular carcinoma (HCC). With this study, we aimed to solve the technical problem of anlotinib being insoluble in injectable solutions; we also aimed to assess the antitumor activity of anlotinib on hepatocellular carcinoma cells. We prepared an anlotinib nanocrystal injection by wet grinding, and we optimized the prescription process using a transmission electron microscope (TEM) and a laser particle size analyzer (LPSA). The release of anlotinib from the injected nanocrystals was evaluated using LC-MS/MS in vitro, and the drug’s anti-tumor effects were assessed in a nude mice tumor model. The anlotinib nanocrystals had a uniform particle size distribution (the average nanoparticle size was 200 nm). The preparation of anlotinib into nanocrystals did not change the original crystal structure. The intravenous injection of anlotinib nanocrystals achieved anti-tumor activity at very low doses compared to those required for oral administration of an anlotinib suspension: anlotinib nanocrystals at a dose of 50 μg/kg inhibited the subcutaneous growth of the HCC cell line MHCC97-H; whereas the dose of anlotinib suspension required for an equivalent effect was 1 mg/kg. Therefore, our novel anlotinib nanocrystal injection preparation provides an option for achieving a safe and effective molecularly targeted therapy against advanced HCC.